The role of phenolics in the interaction between oil palm and Ganoderma boninense the casual agent of basal stem rot - Chong, Khim Phin (2010)
Basal Stem Rot (BSR) of oil palm (EIaeis guineensis) is caused by Ganoderma boninense, and is one of the most commercially devastating diseases in South East Asia. It can kill more than 80 percent of stands by the time they are halfway through their normal economic life. High incidence of BSR results in economic losses, due to zero yield from dead palms and significantly reduced weight and number of fruit bunches in infected but living palms. Many methods have been attempted to control BSR. These include clean clearing, fallow period before re-planting, burning of waste or dead material, windrowing, use of fungicides as soil drenching or by tree injection, surgical removal of infected material, biological control and development of varieties with enhanced resistance. To date no method gives good control of Ganoderma infection in established plantations and some have technical limitations in application. The aim of this study was to investigate a possible source of disease resistance associated with the accumulation of phenolics, after inoculation with G. boninense and elicitation with the biopolymer chitosan. The identity of isolates of Ganoderma from Langkon Oil Palm Estate in Sabah, Malaysia, which were used in this project, was confirmed using Ganoderma Selective Medium and DNA sequence analysis after PCR amplification. That latter method showed that the Sabah isolates were very similar to virulent G. boninense strains FA5017 or FA5035 from West Malaysia, with a maximum similarity of 98%. A method to inoculate oil palm seedlings with Ganoderma, based on root treatment with macerated mycelium, was developed which facilitated experiments with consistent and rapid disease development. This proved an improvement compared to the traditional technique of inoculation with colonised rubber wood blocks. Ekona and Calabar varieties of oil palm were found to be more susceptible to G. boninense infection compared to the variety AVROS, based on a higher accumulation of ergosterol (a fungal sterol) and infection scores based on the Modified Disease Severity Score. Results from both parameters showed a strong correlation between each other and provided a quick assessment on the progress of pathogen infection for use in this project. It should be noted, however, that none of the varieties tested exhibited a high level of disease resistance. Following preliminary studies to quantify the accumulation of total phenolics, using Folin-Ciocalteu reagent, High Performance Liquid Chromatography was used to monitor changes in the concentration of three specific phenolics, which were considered to be of primary importance. These were syringic acid, caffeic acid and 4-hydroxybenzoic acid (4-HBA). Their identification was confirmed using co-injection with pure standards and by LCMS/Q-tof. The variety AVROS showed a slightly higher content of all these three phenolics compared to Ekona and Calabar. Stimulation of their accumulation was promoted by the addition of chitosan to the plant-growing medium. By the end of the time course, the concentration of these phenolics decreased in the oil palm tissues inoculated with G. boninense suggesting possible metabolism by this pathogen. This loss was, however, not detected in tissues elicited with chitosan alone and was greatly reduced when G. boninense was combined with chitosan. In vitro studies on antifungal activity with phenolics incorporated either in 10% Potato Dextose Agar, Oil Palm Root Agar or Oil Palm Root Broth were done, using concentrations (50-110 pg mL 1) of phenolic acids typically detected in oil palm root tissues. Syringic acid was found to be the most antifungal of the phenolics tested. Caffeic acid had lower activity and 4-HBA was virtually inactive. Concentrations of syringic acid detected in root tissues, especially in the presence of chitosan, that might be expected to inhibit growth of G. boninense. The pathogen was shown to be able to degrade all of the phenolic acids tested. However, at the highest concentration tested, metabolism was greatly delayed, only occurring after a lag phase in the growth of pathogen. TLC bioassay showed the degradation products of all these phenolics were no longer antifungal. Thus, accumulation of phenolic acids, especially syringic acid, may provide a useful marker in future breeding of resistant varieties.